Are angiotensin receptor blockers (ARBs) safe to use in patients with a history of angiotensin‐converting enzyme inhibitor (ACEI)‐induced angioedema?. Issue 10 (October 2015) - Wojtusik, Amanda; Lee, Soo Jung; Wilson, Stephen A.
Abstract : Evidence‐Based Answer : The use of an ARB is not contraindicated in patients with a history of ACEI‐induced angioedema. A cautious trial of ARBs by these patients appears to be safe (SOR: B, RCTs).